The Destruction of Maritime Civilization Due to the Punik I War between Kartago and Roman (264 - 241 BC) - Asep Darmawan; Arif Badrudin; Syaiful Anwar; Yusuf Ali; Aris Sarjito (Budapest International Research and Critics University, 2022)
Punik's war or war is a series of wars between Cartago and Rome which occurred between 264sm-146sm and is the largest war in the ancient world. In this modern era, we often find various literature that discusses the importance of controlling the sea to control the world. History also gives us a lesson in how a developed and strong maritime state will be destroyed and even disappear from history, due to reluctance to maintain that power. Based on the foregoing, this study discussed the destruction of maritime civilizations due to the Punik I war between Kartago and Rome (264 - 241 BC). This study uses a descriptive-explicant research approach with a qualitative approach. The research paradigm used is constructivist with researchers as the main research tool. This study uses content analysis techniques and literature research. The results of the study obtained this war had caused the two empires to run out of their wealth. The battles that occurred in the war Punik I became an important milestone that determined the results of the battle in Punik III War. The biggest maritime power in the world has turned down to be continental, while continental power has unfurled its screen to become a strong maritime country. For Indonesia, Punik's war gave Lessons Learned which is very valuable to be a reflection that as a maritime country, we need a visionary statesman to restore the glory of the archipelago.